Associations between pyrethroid exposure and serum sex steroid hormones in adults: Findings from a nationally representative sample. (August 2022) - Xu, Huadong; Bo, Yacong
Abstract: Background: Pyrethroids have been considered as potential endocrine-disrupting chemicals and have been shown to be associated with endocrine-related health outcomes. However, limited studies directly explored the link between pyrethroid exposure and sex hormones in the general population. Objectives: To explore the associations between exposure to pyrethroids and serum sex steroid hormones in adults. Methods: We evaluated the cross-sectional associations in 1235 adults aged ≥20 years who had been assigned to the National Health and Nutrition Examination Survey (NHANES) 2013–2014. The urinary concentration of 3-phenoxybenzoic acid (3-PBA) was applied as a biomarker of human pyrethroid exposure levels. Information on sex steroid hormones, including total testosterone (TT), estradiol (E2), and sex hormone-binding globulin (SHBG) in serum were measured. Free androgen index (FAI) and the ratio of TT to E2 (TT/E2) were also calculated. The percent changes with 95% confidence intervals (CIs) for a doubling of 3-PBA concentrations in the serum sex hormone levels were estimated using generalized linear regression models. Results: The overall median concentrations of creatinine-adjusted 3-PBA were 0.58 μg/g creatinine, and 90.0% of adults had a detectable level of 3-PBA. In females, every two-fold increase in 3-PBA was associated with 4.34% (95% CI: 1.58%, 7.18%) higher levels of TT and 4.05% (95% CI: 7.03%, 1.16%) higher levels of SHBG, respectively. In males, a doubling in 3-PBA was associated with 3.02% (95% CI: 1.21%, 4.86%) increase in SHBG but 1.85% (−3.59%, −0.07%) decrease in FAI, respectively. In addition, significant non-linear associations of 3-PBA with SHBG in both males and females and TT in females were observed. Conclusions: Environmental pyrethroid exposure was associated with altered sex hormones in adults. This study provides important epidemiological evidence for the association of pyrethroids with endocrine disruption. Graphical abstract: Image 1 Highlights: Exposure to pyrethroids is a global health concern. 3-phenoxybenzoic acid (3-PBA) was detected in over 90.0% of adults. Positive non-linear associations of 3-PBA with female TT and SHBG were observed. Correlations of 3-PBA with SHBG or FAI in males were observed. This suggests a potential health effect of pyrethroid exposure on sex hormones.